Upaya Peningkatan Mutu Penerapan Audit Tools and Linked Archives System Terhadap Proses Audit Laporan Keuangan Pada KAP - Tambun, Sihar; Parago, Agnes Do (Universitas 17 Agustus 1945 Jakarta, 2024)
Independent Competency-Based Internship (MBKM) is an integral part of a higher education program that aims to develop the ability to work in groups and communicate with colleagues and clients. The next goal is to learn about audit planning for the Company's financial statements. Furthermore, to learn about audit procedures in Public Accounting Firms and to increase insight and knowledge as well as experience in the field of Accounting in Public Accounting Firms. This MBKM Internship Program uses the project-based learning method, which is a method that requires students to focus on tasks programmed together with the supervisor and guided by the supervisor at the internship location. The stages carried out are the first to search for an internship location, the second to conduct interviews, the third to carry out internship activities, and to identify potential improvements in the quality of the application of audit tools, the fourth to make internship reports and journals. This internship program has succeeded in improving the competence of student interns, gaining applicable experience and greatly helping students to be better prepared to face the world of work in the future.